MODIFIKASI SISTEM TRANSMISI MESIN ELASTIS UNTUK MENINGKATKAN KAPASITAS PRODUKSI - Asmungi Asmungi; Naradzar Wahyu Saputro (LPPM Universitas Bina Bangsa, 2023)
Fulfilling production demand is a must for any manufacturing industry anywhere, in this case the company wants to increase the production capacity of elastic machine A, where during production the target has never been met, this is due to limited machine capacity, with a percentage of 71.6% in meeting production targets and an overall equipment effectiveness (OEE) value or machine effectiveness of 71.2%. To increase this capacity is influenced by the spinning speed on the machine, the faster the rotation, the faster the production, to speed up the rotation, it is necessary to modify the transmission system, changing the pulley in the transmission system can affect the speed, the pulley size is changed from 110mm to 120mm which causes the spinning speed to increase so that the machine capacity increases, the percentage of production results after modification is 96.9% and increases the percentage of OEE value to 95.16%.